Crystal form of pyrimidine derivative and method for preparing the same
Patent Information
- Application Number
- CN202110696953.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-06-23
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2041-06-23
AI Technical Summary
[0010]目前,现有技术中还没有公开式I化合物的具有令人满意的稳定性的形式,也没有式I化合物晶型方面的报道
Smart Images

Figure CN115504965B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of chemical pharmaceuticals. Specifically, this invention relates to new crystal forms A, B, C, D, and E of N-(2-((6-(3-(2,6-dichloro-3,5-dimethoxyphenyl)-1-methylureido)pyrimidin-4-yl)amino)-5-(4-ethyl-4,7-diazaspiro[2.5]octane-7-yl)phenyl)acrylamide and their preparation methods. Background Technology
[0002] The fibroblast growth factor receptor (FGFR) family consists of four members (FGFR1, FGFR2, FGFR3, and FGFR4), belonging to the receptor tyrosine kinase family. FGF binding leads to FGFR dimerization, followed by receptor autophosphorylation and activation of downstream signaling pathways. Receptor activation is sufficient to restore and activate specific downstream signaling partners involved in diverse processes such as cell growth, cell metabolism, and cell survival. Therefore, the FGF / FGFR signaling pathway plays a multi-effect role in many biological processes crucial for tumor cell proliferation, migration, invasion, angiogenesis, and cell function. The four members of the FGFR family differ from each other in ligand affinity and tissue distribution. The FGFR-4 gene has a genomic structure containing 18 exons.
[0003] The human FGF19 gene is located at 11q13.1. FGFR4, through specific binding to its ligand FGF19, inhibits apoptosis and NF-κB signaling, and upregulates the expression of genes related to cell proliferation. Activation of FGFR4 in TNF-α-treated cells leads to a decrease in IκB activity, accompanied by a reduction in NF-κB distribution and a weakening of apoptosis. All four FGFR genes are expressed in the human liver, but mature hepatocytes (Hepatopyte) express only FGFR4 in large quantities. The binding of FGFR4 and its ligand can also regulate bile acid metabolism. The balance between cholesterol and bile acid conversion in the body is closely related to various normal physiological functions. Disruption of this balance can cause various diseases such as fatty liver and cardiovascular diseases like arteriosclerosis. Therefore, the interaction between FGFR4 and FGF19 has become a new target for cholesterol-lowering drugs for hyperlipidemia.
[0004] In recent years, increasing evidence has shown that FGFR1, FGFR2, FGFR3 and FGFR4 gene amplification mutations exist in many types of cancer. Extensive evidence suggests that FGFR1 has gene mutations in breast cancer, non-small cell lung cancer, and glioblastoma, and fusion proteins formed by gene transposition in acute myeloid leukemia. It is also overexpressed in pancreatic cancer, bladder cancer, prostate cancer, and esophageal cancer. FGFR2 has gene mutations and amplifications in gastric cancer, breast cancer, and uterine cancer, and is also overexpressed in prostate cancer, esophageal cancer, ovarian cancer, pancreatic cancer, brain tumors, and colorectal cancer. FGFR3 has gene mutations in multiple myeloma and bladder cancer, and is overexpressed in ovarian cancer, non-small cell lung cancer, and hepatocellular carcinoma. FGFR4 has mutations and overexpression in lung cancer, ovarian cancer, prostate cancer, liver cancer, and bile duct cancer, and is also overexpressed in thyroid cancer and ovarian cancer (French et al. 2012 PLos ONE7(5): e367313; Sia et al. 2013 Gastrojterology 144: 829-840).
[0005] A series of FGFR inhibitor patents have been published, but fewer patents have been published for selective FGFR4 inhibition. Selective FGFR4 inhibitors have the advantage of lower toxicity compared to FGFR inhibitors (Brown, AP et al. (2005), Toxocol. Pathol., 449-455). Currently, FGFR4 inhibitors in clinical trials include FGF-401 (Novartis, Phase II clinical trial), BLU-554 (Blueprint, Phase I clinical trial), and H3B6527 (Eisai, Phase I clinical trial). Patents for selective FGFR4 inhibition include WO2015059668, WO2015057938, and WO2015057963. Current research on FGFR4 inhibitors for treating liver cancer and other tumors is far from sufficient, and further research and development of new FGFR4 inhibitors are still necessary.
[0006] WO2017198221A1 discloses pyrimidine derivatives having the structure of formula I, with the molecular formula C. 31 H 36 Cl2N8O4; its chemical name is: N-(2-((6-(3-(2,6-dichloro-3,5-dimethoxyphenyl)-1-methylureido)pyrimidin-4-yl)amino)-5-(4-ethyl-4,7-diazaspiro[2.5]octane-7-yl)phenyl)acrylamide.
[0007]
[0008] However, the white solid obtained by the preparation method of the above-mentioned Formula I compound disclosed in WO2017198221A1 is in an amorphous form, and its stability, particle size, flowability, and hygroscopicity are still not satisfactory. Specifically, its particle size is small and its flowability is poor, making it unsuitable for the forming process of solid dosage forms (such as tablets, capsules, or granules). In addition, the better the stability, the greater the benefit to the later use of Formula I. For example, the production of solid dosage forms requires the stability of the active pharmaceutical ingredient, and the active pharmaceutical ingredient and the finished product need to maintain the quality stability of the product over a long shelf life.
[0009] The preparation of dosage forms facilitates the accurate delivery of precise doses of medicine. However, the ease of preparing dosage forms is known to depend on factors such as, but not limited to, the solubility, homogeneity, hygroscopicity, and flowability of the drug. Therefore, a crystal form of a Formula I compound with excellent properties is required.
[0010] Currently, there is no publicly available form of compound I with satisfactory stability, nor are there any reports on the crystal form of compound I. Through extensive experimentation, the inventors have obtained the crystal form of compound I. Summary of the Invention
[0011] Therefore, in view of the problems existing in the prior art, the present invention provides the crystal form of compound N-(2-((6-(3-(2,6-dichloro-3,5-dimethoxyphenyl)-1-methylureido)pyrimidin-4-yl)amino)-5-(4-ethyl-4,7-diazaspiro[2.5]octane-7-yl)phenyl)acrylamide of formula I and its preparation method.
[0012]
[0013] In a first aspect, the present invention provides a crystal form A (hereinafter referred to as "crystal form A") of a compound of formula I.
[0014] The crystal form A, when subjected to Cu-Kα radiation, exhibits characteristic peaks in its X-ray powder diffraction pattern at 7.3±0.2°, 8.4±0.2°, 9.7±0.2°, 12.4±0.2°, 16.7±0.2°, and 19.5±0.2°, expressed in degrees.
[0015] Preferably, the crystal form A, when subjected to Cu-Kα radiation, exhibits characteristic peaks in its X-ray powder diffraction pattern (expressed in degrees) at 7.3±0.2°, 8.4±0.2°, 9.7±0.2°, 12.4±0.2°, 16.7±0.2°, 19.5±0.2°, 21.7±0.2°, 23.5±0.2°, and 28.6±0.2°.
[0016] More preferably, the crystal form A, when subjected to Cu-Kα radiation, exhibits a characteristic peak and relative intensity at the following positions in its X-ray powder diffraction pattern, expressed in degrees as 2θ:
[0017] Table 1
[0018]
[0019]
[0020] More preferably, the X-ray powder diffraction pattern of crystal form A is substantially as follows: Figure 1 As shown.
[0021] Furthermore, the differential scanning calorimetry (DSC) spectrum of crystal form A shows an endothermic peak at 208-212℃, and the DSC spectrum is essentially as follows. Figure 2 As shown.
[0022] Accordingly, the present invention provides a method for preparing crystal form A, wherein the method may be selected from any of the following methods:
[0023] Method (1): Mix the compound of formula I with an organic solvent to obtain a suspension. Stir the suspension at 5-50℃ for 1-7 days, separate the solid, and vacuum dry at 20-60℃ for 8-24 hours to obtain crystal form A. The organic solvent is selected from one or more of C1-C3 alcohols, methyl acetate, ethyl acetate, acetone, and acetonitrile.
[0024] Preferably, the C1-C3 alcohols in method (1) are selected from methanol, ethanol, n-propanol or isopropanol;
[0025] Preferably, the weight-to-volume ratio of the compound of formula I to the organic solvent in method (1) is 1:2-1:50 (g / mL);
[0026] Method (2): Mix the compound of formula I with DMSO or dichloromethane, stir at 20-50℃ until dissolved, add a poor solvent, stir to crystallize, separate the solid, and vacuum dry at 20-60℃ for 8-24h to obtain crystal form A. The poor solvent is selected from one or more of C1-C4 alcohols, methyl acetate, ethyl acetate, butyl acetate, isopropyl acetate, acetone, acetonitrile, water, and alkanes.
[0027] Preferably, the C1-C4 alcohol in method (2) is selected from methanol, ethanol or isopropanol, and the alkane is selected from n-heptane, n-hexane or cyclohexane;
[0028] Preferably, the weight-to-volume ratio of the compound of formula I in method (2) to DMSO or dichloromethane is 1:10-1:40 (g / mL);
[0029] Preferably, the weight-to-volume ratio of the compound of formula I to the unsuitable solvent in method (2) is 1:20-1:130 (g / mL);
[0030] Method (3): Mix the compound of formula I with DMF, stir at 20-50℃ until dissolved, add a poor solvent, stir to crystallize, separate the solid, and vacuum dry at 20-60℃ for 8-24h to obtain crystal form A;
[0031] Preferably, the undesirable solvent in method (3) is selected from one or more of C2-C4 alcohols, isopropyl acetate, acetone, acetonitrile, and water;
[0032] Preferably, the C2-C4 alcohol in method (3) is selected from ethanol or isopropanol;
[0033] Preferably, the weight-to-volume ratio of the compound of formula I to DMF in method (3) is 1:5-1:20 (g / mL);
[0034] Preferably, the weight-to-volume ratio of the compound of formula I to the unsuitable solvent in method (3) is 1:20-1:100 (g / mL);
[0035] Method (4): Mix the compound of formula I with DMAC, stir at 20-50℃ until dissolved, add a poor solvent, stir to crystallize, separate the solid, and vacuum dry at 20-60℃ for 8-24h to obtain crystal form A. The weight-volume ratio of the compound of formula I to DMAC is 1:6-1:30 (g / mL).
[0036] Preferably, the undesirable solvent in method (4) is selected from one or more of C1-C4 alcohols and water;
[0037] Preferably, the C1-C4 alcohol in method (4) is selected from methanol, ethanol or isopropanol;
[0038] Preferably, the weight-to-volume ratio of the compound of formula I to the unsuitable solvent in method (4) is 1:20-1:100 (g / mL);
[0039] Method (5): Mix the compound of formula I with n-butanol to obtain a suspension. Stir the suspension at 5-40℃ for 1-7 days, separate the solid, and vacuum dry at 20-60℃ for 8-24 hours to obtain crystal form A.
[0040] Preferably, the weight-to-volume ratio of the compound of formula I to the solvent in method (5) is 1:2 to 1:50 (g / mL).
[0041] In another aspect, the present invention provides crystal form B of the compound of formula I (hereinafter referred to as "crystal form B").
[0042] The crystal form B, when subjected to Cu-Kα radiation, exhibits characteristic peaks in its X-ray powder diffraction pattern at 7.9±0.2°, 9.4±0.2°, 10.1±0.2°, 11.9±0.2°, 14.4±0.2°, 16.1±0.2°, and 19.0±0.2°, expressed in degrees.
[0043] Preferably, the crystal form B, when subjected to Cu-Kα radiation, exhibits characteristic peaks in its X-ray powder diffraction pattern (expressed in degrees) at 7.9±0.2°, 9.4±0.2°, 10.1±0.2°, 11.9±0.2°, 14.4±0.2°, 16.1±0.2°, 16.9±0.2°, 19.0±0.2°, 19.3±0.2°, 21.7±0.2°, and 22.4±0.2°.
[0044] More preferably, the crystal form B, when subjected to Cu-Kα radiation, exhibits a characteristic peak and relative intensity at the following positions in its X-ray powder diffraction pattern, expressed in degrees as 2θ:
[0045] Table 2
[0046]
[0047]
[0048] More preferably, the X-ray powder diffraction pattern of crystal form B is substantially as follows: Figure 3 Show.
[0049] Furthermore, the differential scanning calorimetry (DSC) spectrum of crystal form B exhibits an endothermic peak at 195-201℃, and the DSC spectrum is essentially as follows. Figure 4 As shown.
[0050] Accordingly, the present invention provides a method for preparing crystal form B, wherein the method is selected from any one of the following methods:
[0051] Method (1): Mix the compound of formula I with dichloromethane, stir at 20-30℃ until dissolved, add a poor solvent, stir to crystallize, separate the solid, and vacuum dry at 20-60℃ for 8-24h to obtain crystal form B. The poor solvent is a mixture of isobutyl acetate and n-heptane.
[0052] Preferably, the weight-to-volume ratio of the compound of formula I in method (1) to dichloromethane is 1:10-1:30 (g / mL);
[0053] Preferably, the weight-to-volume ratio of the compound of formula I in method (1) to the unsuitable solvent is 1:20-1:100 (g / mL).
[0054] Method (2): Mix the compound of formula I with a solvent to obtain a suspension. Stir the suspension at 5-50℃ for 1-7 days, separate the solid, and vacuum dry at 20-60℃ for 8-24 hours to obtain crystal form B. The solvent is selected from one or more of 2-butanone, methyl isobutyl ketone, 1,4-dioxane, butyl acetate, isopropyl acetate, isobutyl acetate, n-heptane, n-hexane, cyclohexane, and water.
[0055] Preferably, the weight-to-volume ratio of the compound of formula I to the solvent in method (2) is 1:2 to 1:50 (g / mL).
[0056] In another aspect, the present invention provides crystal form C of the compound of formula I (hereinafter referred to as "crystal form C").
[0057] The crystal form C, when subjected to Cu-Kα radiation, exhibits characteristic peaks in its X-ray powder diffraction pattern, expressed in degrees, at 2θ at 7.3±0.2°, 12.4±0.2°, 12.8±0.2°, 14.8±0.2°, 18.4±0.2°, 19.5±0.2°, and 23.0±0.2°.
[0058] Preferably, the crystal form C, when subjected to Cu-Kα radiation, exhibits characteristic peaks in its X-ray powder diffraction pattern (expressed in degrees) at 7.3±0.2°, 12.4±0.2°, 12.8±0.2°, 14.8±0.2°, 18.4±0.2°, 19.5±0.2°, 20.8±0.2°, 23.0±0.2°, 23.3±0.2°, 24.3±0.2°, and 26.0±0.2°.
[0059] More preferably, the crystal form C, when subjected to Cu-Kα radiation, exhibits a characteristic peak and relative intensity at the following positions in its X-ray powder diffraction pattern, expressed in degrees as 2θ:
[0060] Table 3
[0061]
[0062]
[0063] More preferably, the X-ray powder diffraction pattern of crystal form C is substantially as follows: Figure 5 Show.
[0064] Furthermore, the differential scanning calorimetry (DSC) spectrum of the crystal form C exhibits an endothermic peak at 161-168℃, and the DSC spectrum is essentially as follows. Figure 6 As shown.
[0065] Accordingly, the present invention provides a method for preparing crystal form C, wherein the method may be selected from any of the following methods:
[0066] Method (1): Mix the compound of formula I with DMAC to obtain a suspension. Stir the suspension at 50-70℃ for 8-24h, separate the solid, and vacuum dry at 20-60℃ for 8-24h to obtain crystal form C. The weight-volume ratio of the compound of formula I to DMAC is 1:2-1:5 (g / mL).
[0067] Method (2): Mix the compound of formula I with DMAC, stir at 55-70℃ until dissolved, add a poor solvent, stir to crystallize, separate the solid, and vacuum dry at 20-60℃ for 8-24h to obtain crystal form C. The weight-volume ratio of the compound of formula I to DMAC is 1:6-1:30 (g / mL).
[0068] Preferably, the undesirable solvent in method (2) is selected from n-propanol, isopropanol, n-butanol, C3-C6 ester or acetone;
[0069] Preferably, the C3-C6 ester in method (2) is selected from methyl acetate, ethyl acetate, isopropyl acetate or isobutyl acetate;
[0070] Preferably, the weight-to-volume ratio of the compound of formula I to the unsuitable solvent in method (2) is 1:10-1:50 (g / mL).
[0071] In another aspect, the present invention provides a crystal form D (hereinafter referred to as "crystal form D") of the compound of formula I.
[0072] The crystal form D, when subjected to Cu-Kα radiation, exhibits characteristic peaks in its X-ray powder diffraction pattern at 3.5±0.2°, 7.0±0.2°, 13.4±0.2°, 15.7±0.2°, 16.6±0.2°, and 20.6±0.2°, expressed in degrees.
[0073] Preferably, the crystal form D, when subjected to Cu-Kα radiation, exhibits characteristic peaks in its X-ray powder diffraction pattern (expressed in degrees) at 3.5±0.2°, 7.0±0.2°, 12.0±0.2°, 13.4±0.2°, 15.7±0.2°, 16.6±0.2°, 20.1±0.2°, 20.6±0.2°, 22.1±0.2°, and 24.9±0.2°.
[0074] More preferably, the crystal form D, when subjected to Cu-Kα radiation, exhibits a characteristic peak and relative intensity at the following positions in its X-ray powder diffraction pattern, expressed in degrees as 2θ:
[0075] Table 4
[0076]
[0077]
[0078] More preferably, the X-ray powder diffraction pattern of the crystal form D is substantially as follows: Figure 7 Show.
[0079] Furthermore, the differential scanning calorimetry (DSC) spectrum of crystal form D shows an endothermic peak at 150-158℃, and the DSC spectrum is basically as follows. Figure 8 As shown.
[0080] Accordingly, the present invention provides a method for preparing crystal form D, the method comprising:
[0081] The compound of formula I was mixed with DMF and stirred at 50-70℃ until dissolved. Methanol was added, and the mixture was cooled to 20-30℃ and stirred to crystallize. The solid was separated and dried under vacuum at 20-60℃ for 8-24 hours to obtain crystal form D.
[0082] Preferably, the weight-to-volume ratio of the compound of formula I to DMF is 1:10-1:30 (g / mL);
[0083] Preferably, the weight-to-volume ratio of the compound of Formula I to methanol is 1:20-1:50 (g / mL).
[0084] In another aspect, the present invention provides a crystal form E (hereinafter referred to as "crystal form E") of the compound of formula I.
[0085] The crystal form E, when subjected to Cu-Kα radiation, exhibits characteristic peaks in its X-ray powder diffraction pattern, expressed in degrees, at 2θ at 3.5±0.2°, 7.0±0.2°, 13.5±0.2°, 15.2±0.2°, 16.3±0.2°, 17.5±0.2°, and 28.7±0.2°.
[0086] Preferably, the crystal form E, when subjected to Cu-Kα radiation, exhibits characteristic peaks in its X-ray powder diffraction pattern (expressed in degrees) at 3.5±0.2°, 7.0±0.2°, 13.5±0.2°, 15.2±0.2°, 16.3±0.2°, 17.5±0.2°, 18.8±0.2°, 20.2±0.2°, 22.1±0.2°, 25.0±0.2°, and 28.7±0.2°.
[0087] More preferably, the crystal form E, when subjected to Cu-Kα radiation, exhibits a characteristic peak and relative intensity at the following positions in its X-ray powder diffraction pattern, expressed in degrees as 2θ:
[0088] Table 5
[0089]
[0090]
[0091] More preferably, the X-ray powder diffraction pattern of the crystal form E is substantially as follows: Figure 9 As shown.
[0092] Furthermore, the differential scanning calorimetry (DSC) spectrum of crystal form E exhibits an endothermic peak at 131-145℃, and the DSC spectrum is essentially as follows. Figure 10 As shown.
[0093] Accordingly, the present invention provides a method for preparing crystal form E, wherein the method may be selected from any of the following methods:
[0094] Method (1): Mix the compound of formula I with DMF, stir at 20-30℃ until dissolved, then add back to a poor solvent, stir to crystallize, separate the solid, and vacuum dry at 20-60℃ for 8-24h to obtain crystal form E;
[0095] The unsuitable solvents mentioned in method (1) are selected from ethanol, acetone, acetonitrile and water mixtures;
[0096] Preferably, the weight-to-volume ratio of the compound of formula I to DMF in method (1) is 1:5-1:20 (g / mL);
[0097] Preferably, the weight-to-volume ratio of the compound of formula I in method (1) to the unsuitable solvent is 1:20-1:100 (g / mL).
[0098] Method (2): Mix the compound of formula I with DMAC, stir and dissolve at 20-30℃, then add back to a poor solvent, stir to crystallize, separate the solid, and vacuum dry at 20-60℃ for 8-24h to obtain crystal form E. The weight-volume ratio of the compound of formula I to DMAC is 1:6-1:30 (g / mL).
[0099] Preferably, the undesirable solvent in method (2) is selected from a mixture of ethanol, n-propanol and water;
[0100] Preferably, the weight-to-volume ratio of the compound of Formula I to the unsuitable solvent is 1:70-1:100 (g / mL).
[0101] In another aspect, the present invention provides a pharmaceutical composition containing a therapeutically effective amount of crystal form A, B, C, D, or E as an active ingredient. Preferably, in the pharmaceutical composition, crystal form A, B, C, D, or E can be mixed with one or more pharmaceutically acceptable solid or liquid diluents and / or excipients to form a galenine formulation.
[0102] In another aspect, the present invention provides the use of crystal form A or crystal form B or crystal form C or crystal form D or crystal form E or a pharmaceutical composition thereof in the preparation of a medicament for treating cancer, wherein said disease is non-small cell lung cancer, gastric cancer, multiple myeloma, liver cancer, cholangiocarcinoma, preferably liver cancer and cholangiocarcinoma. Attached image description:
[0103] Figure 1 The X-ray powder diffraction pattern of crystal form A was prepared for Example 1.
[0104] Figure 2 The DSC spectrum of crystal form A was prepared for Example 1.
[0105] Figure 3 The X-ray powder diffraction pattern of crystal form B was prepared for Example 32.
[0106] Figure 4 The DSC spectrum of crystal form B was prepared for Example 32.
[0107] Figure 5 The X-ray powder diffraction pattern of crystal form C was prepared for Example 48.
[0108] Figure 6 The DSC spectrum of the crystal form C was prepared for Example 48.
[0109] Figure 7 The X-ray powder diffraction pattern of crystal form D was prepared for Example 51.
[0110] Figure 8 The DSC spectrum of the crystal form D was prepared for Example 51.
[0111] Figure 9 The X-ray powder diffraction pattern of crystal form E was prepared for Example 54.
[0112] Figure 10 The DSC spectrum of crystal form E was prepared for Example 54.
[0113] Figure 11 The X-ray powder diffraction pattern of the white amorphous solid obtained in the preparation example. Detailed Implementation
[0114] The present invention will be described in further detail below. It should be understood that the terms used are for descriptive purposes and not for limiting the invention.
[0115] General definitions and terms
[0116] Unless otherwise stated, the technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. In case of any conflict, the definitions provided herein shall prevail. When a quantity, concentration, or other value or parameter is expressed as a range, preferred range, or preferred upper and lower numerical limits, it should be understood that this is equivalent to specifically disclosing any range by combining any pair of upper or preferred values with any lower or preferred value, regardless of whether the range is specifically disclosed. Unless otherwise stated, the numerical ranges listed herein are intended to include the endpoints of the range and all integers and fractions (decimals) within that range.
[0117] When used with a numerical variable, the terms "about" or "approximately" usually mean that the value of the variable and all values of the variable are within the experimental error (e.g., within a 95% confidence interval for the mean) or within ±10% of the specified value, or a wider range.
[0118] The expression "comprising," or similar expressions such as "including," "containing," and "having," is open-ended and does not exclude additional unlisted elements, steps, or components. The expression "consisting of," excludes any unspecified elements, steps, or components. The expression "substantially consisting of," limits the scope to the specified elements, steps, or components, plus optional elements, steps, or components that do not materially affect the essential and novel features of the claimed subject matter. It should be understood that the expression "comprising" encompasses both the expressions "substantially consisting of" and "consisting of."
[0119] As used herein, the terms “optional” or “optionally” mean that the event or situation subsequently described may or may not occur, including both the occurrence and non-occurrence of the event or situation.
[0120] Unless otherwise stated, percentages, parts, etc. in this document are by weight.
[0121] As used herein, the term “crystal form” or “crystal” refers to any solid material exhibiting a three-dimensional arrangement, as opposed to amorphous solid materials, which produce characteristic X-ray powder diffraction patterns with well-defined peaks.
[0122] As used herein, the term “X-ray powder diffraction (XRPD) pattern” refers to an experimentally observed diffraction pattern or the parameters, data, or values derived from it. XRPD patterns are typically characterized by peak position (x-axis) and / or peak intensity (y-axis).
[0123] As used herein, the term "2θ" refers to the peak position in degrees (°) based on the setup of an X-ray diffraction experiment, and is typically the horizontal axis unit in a diffraction pattern. If the incident beam is diffracted when it forms an angle θ with a lattice plane, the experimental setup requires recording the reflected beam at a 2θ angle. It should be understood that specific 2θ values for a particular crystal form mentioned herein are intended to represent 2θ values (in degrees) measured using the X-ray diffraction experimental conditions described herein. For example, as described herein, using Cu-Kα (Kα1 is... The XRPD spectra in this paper can be acquired, for example, on a Rigaku MiniFlex-600 X-ray powder diffractometer. Exemplary test conditions could be a scan speed of 10° / min and a scan step size of 0.01°.
[0124] As used herein, the term "substantially" for X-ray diffraction peaks means taking into account representative peak position and intensity variations. For example, those skilled in the art will understand that peak position (2θ) will show some variation, typically up to 0.1–0.2 degrees (±0.1 to ±0.2 degrees), and the instrument used to measure diffraction will also cause some variation. Furthermore, those skilled in the art will understand that relative peak intensities will vary due to instrumental differences, degree of crystallinity, preferred orientation, the prepared sample surface, and other factors known to those skilled in the art, and should be considered as qualitative measurements only.
[0125] As used herein, differential scanning calorimetry (DSC) determines the transition temperatures when a crystal absorbs or releases heat due to a change in its crystal structure or melting. For the same crystal form of the same compound, the error in thermal transition temperature and melting point is typically within about 5 °C in successive analyses. When describing a compound as having a given DSC peak or melting point, this refers to that DSC peak or melting point ±5 °C. This temperature variation is also taken into account “substantially”. DSC provides an auxiliary method for distinguishing different crystal forms. Different crystal forms can be identified based on their different transition temperature characteristics. It should be noted that for mixtures, their DSC peaks or melting points may vary over a wider range. Furthermore, since decomposition occurs during the melting process, the melting temperature is related to the heating rate. DSC spectra can be measured, for example, on an instrument such as the NETZSCH DSC214. Exemplary test conditions are a heating rate of 10 °C / min and a temperature range of 25–250 °C.
[0126] Beneficial effects
[0127] The crystallization process of the compound of formula I of this invention is simple, easy to operate, and can be industrialized. Moreover, the crystal form drug of this invention has the advantages of high product purity, excellent physicochemical properties, good high temperature / high humidity and chemical and physical stability, excellent processing (filtration, drying, dissolution and tableting) adaptability, reproducibility, low hygroscopicity and good flowability. It is more conducive to the processing of drugs and the improvement of drug performance. In addition, it has good solubility, dissolution rate, dissolution time and biological release, and has a good market application prospect.
[0128] The following examples further illustrate the present invention, and are intended only to provide a better understanding of the invention. They do not constitute a limitation or restriction on the scope of protection of the present invention.
[0129] Preparation and characterization of the crystal form of compound I
[0130] Preparation Example
[0131] The compound of formula I described in this invention embodiment was prepared according to the method in Example 5 of patent WO2017198221A1, namely, tert-butyl-N-[6-[[tert-butoxycarbonyl(2,6-dichloro-3,5-dimethoxy-phenyl)carbamoyl]methylamino]pyrimidin-4-yl]-N-[4-(8-ethyl-5,8-diazaspiro[2.5]octane-5-yl)-2(prop-2-enoylamino)phenyl]carbamate 5i (440 mg, 0.514 mmol) was dissolved in 15 mL of dichloromethane, 5 mL of trifluoroacetic acid was added, and the reaction was carried out at room temperature for 12 hours. The reaction solution was concentrated under reduced pressure, and 20 mL of ethyl acetate was added. The solution was washed successively with 20 mL of saturated sodium carbonate solution and 20 mL of saturated sodium chloride solution, dried over anhydrous sodium sulfate, filtered, and concentrated under reduced pressure. The residue was purified by silica gel thin-layer chromatography (eluent: system B) to obtain N-(2-((6-(3-(2,6-dichloro-3,5-dimethoxyphenyl)-1-methylureido)pyrimidin-4-yl)amino)-5-(4-ethyl-4,7-diazaspiro[2,5]octane-7-yl)phenyl)acrylamide 5 (100 mg, white solid). The obtained white solid was XRPD analyzed and found to be amorphous. Its X-ray powder diffraction pattern is shown below. Figure 11 As shown.
[0132] Test instrument information and methods
[0133] The X-ray powder diffraction instrument and testing conditions involved in this invention are as follows: X-ray diffraction instrument model: RigakuMiniFlex-600 Cu target; operation method: scanning speed 10° / min, scanning step width 0.01°.
[0134] The DSC test conditions involved in this invention are as follows: DSC instrument model: NETZSCH DSC214; operating method: heating rate 10℃ / min, temperature range: 25-250℃.
[0135] The high-performance liquid chromatography (HPLC) test conditions involved in this invention are as follows: HPLC instrument model: Agilent 1260; chromatographic column: Waters XBridge C18 150*4.6mm 3.5μm; detection wavelength: 234nm; column temperature: 25℃.
[0136] Example 1: Preparation of Crystal Form A
[0137] 0.1 g of compound I was mixed with 0.2 mL of methanol to obtain a suspension, which was stirred at 5 °C for one day. The solid was separated, and the filter cake was dried under vacuum at 50 °C for 24 h to obtain 0.082 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern are shown below. Figure 1-2 As shown.
[0138] Example 2 Preparation of crystal form A
[0139] 0.1 g of compound I was mixed with 5 mL of ethanol to obtain a suspension, which was stirred at 50 °C for three days. The solid was separated, and the filter cake was dried under vacuum at 50 °C for 24 h to obtain 0.078 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern were respectively compared with those of the compound I. Figure 1-2 Consistent.
[0140] Example 3 Preparation of crystal form A
[0141] 0.1 g of compound I was mixed with 1 mL of isopropanol to obtain a suspension, which was stirred at 25 °C for one day. The solid was separated, and the filter cake was vacuum dried at 50 °C for 24 h to obtain 0.075 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern were respectively compared with those of the compound I. Figure 1-2 Consistent.
[0142] Example 4 Preparation of crystal form A
[0143] 0.1 g of compound I was mixed with 2 mL of n-butanol to obtain a suspension, which was stirred at 25 °C for five days. The solid was separated, and the filter cake was vacuum dried at 40 °C for 24 h to obtain 0.072 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern were respectively compared with those of the compound I. Figure 1-2 Consistent.
[0144] Example 5 Preparation of crystal form A
[0145] 0.1 g of compound I was mixed with 0.5 mL of methyl acetate to obtain a suspension, which was stirred at 30 °C for one day. The solid was separated, and the filter cake was vacuum dried at 20 °C for 24 h to obtain 0.067 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern were respectively compared with those of the compound I. Figure 1-2 Consistent.
[0146] Example 6 Preparation of crystal form A
[0147] 0.1 g of compound I was mixed with 4 mL of ethyl acetate to obtain a suspension. The mixture was stirred at 50 °C for one day. The solid was separated, and the filter cake was dried under vacuum at 60 °C for 24 h to obtain 0.068 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern were compared with those of compound I. Figure 1-2 Consistent.
[0148] Example 7 Preparation of Crystal Form A
[0149] 0.1 g of compound I was mixed with 5 mL of n-propanol to obtain a suspension, which was stirred at 22 °C for one day. The solid was separated, and the filter cake was vacuum dried at 30 °C for 24 h to obtain 0.075 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern were respectively compared with those of the compound I. Figure 1-2 Consistent.
[0150] Example 8 Preparation of crystal form A
[0151] 0.1 g of compound I was mixed with 4 mL of acetone to obtain a suspension, which was stirred at 50 °C for one day. The solid was separated, and the filter cake was vacuum dried at 50 °C for 24 h to obtain 0.056 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with those of compound I. Figure 1-2 Consistent.
[0152] Example 9 Preparation of crystal form A
[0153] 0.1 g of compound I was mixed with 5 mL of acetonitrile to obtain a suspension, which was stirred at 30 °C for seven days. The solid was separated, and the filter cake was vacuum dried at 30 °C for 24 h to obtain 0.066 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern were respectively compared with those of the compound I. Figure 1-2 Consistent.
[0154] Example 10 Preparation of crystal form A
[0155] 0.1 g of compound I was mixed with 1 mL of methanol and 1 mL of ethanol to obtain a suspension. The mixture was stirred at 15 °C for two days. The solid was separated, and the filter cake was dried under vacuum at 50 °C for 12 h to obtain 0.064 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern are shown below. Figure 1-2 As shown.
[0156] Example 11 Preparation of Crystal Form A
[0157] 0.1 g of compound I was mixed with 0.5 mL of methyl acetate and 1 mL of ethyl acetate to obtain a suspension. The mixture was stirred at 20 °C for four days. The solid was separated, and the filter cake was dried under vacuum at 50 °C for 8 hours to obtain 0.071 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern are shown below. Figure 1-2 As shown.
[0158] Example 12 Preparation of Crystal Form A
[0159] 0.1 g of compound I was mixed with 3 mL of DMSO and stirred at 20 °C until dissolved. 5 mL of water was added, and the mixture was stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 50 °C for 24 h to obtain 0.065 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with... Figure 1-2 Consistent.
[0160] Example 13 Preparation of crystal form A
[0161] 0.1 g of compound I was mixed with 2 mL of DMSO and stirred at 25 °C until dissolved. 3 mL of ethanol and 5 mL of water were added, and the mixture was stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 50 °C for 12 h to obtain 0.055 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with… Figure 1-2 Consistent.
[0162] Example 14 Preparation of Crystal Form A
[0163] 0.1 g of compound I was mixed with 4 mL of DMSO and stirred at 30 °C until dissolved. 3 mL of ethyl acetate and 10 mL of water were added, and the mixture was stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 60 °C for 8 h to obtain 0.058 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with... Figure 1-2 Consistent.
[0164] Example 15 Preparation of Crystal Form A
[0165] 0.1 g of compound I was mixed with 1 mL of DMSO and stirred at 50 °C until dissolved. 2 mL of acetonitrile was added, and the mixture was stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 20 °C for 24 h to obtain 0.067 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with... Figure 1-2 Consistent.
[0166] Example 16 Preparation of Crystal Form A
[0167] 0.1 g of compound I was mixed with 1 mL of dichloromethane and stirred at 30 °C until dissolved. 1 mL of methanol and 5 mL of n-heptane were added, and the mixture was stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 40 °C for 12 h to obtain 0.056 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with... Figure 1-2 Consistent.
[0168] Example 17 Preparation of Crystal Form A
[0169] 0.1 g of compound I was mixed with 4 mL of dichloromethane and stirred at 20 °C until dissolved. 5 mL of n-heptane was added, and the mixture was stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 50 °C for 24 h to obtain 0.063 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with... Figure 1-2 Consistent.
[0170] Example 18 Preparation of Crystal Form A
[0171] 0.1 g of compound I was mixed with 2 mL of DMF and stirred at 22 °C until dissolved. 2 mL of isopropanol and 5 mL of water were added, and the mixture was stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 60 °C for 8 h to obtain 0.057 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with… Figure 1-2 Consistent.
[0172] Example 19 Preparation of Crystal Form A
[0173] 0.1 g of compound I was mixed with 1 mL of DMF and stirred at 30 °C until dissolved. 5 mL of isopropyl acetate was added, and the mixture was stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 40 °C for 10 h to obtain 0.055 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with... Figure 1-2 Consistent.
[0174] Example 20 Preparation of crystal form A
[0175] 0.1 g of compound I was mixed with 1 mL of DMF and stirred at 50 °C until dissolved. 3 mL of acetonitrile was added, and the mixture was stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 60 °C for 24 h to obtain 0.048 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with… Figure 1-2 Consistent.
[0176] Example 21 Preparation of crystal form A
[0177] 0.1 g of compound I was mixed with 1 mL of DMF and stirred at 50 °C until dissolved. 5 mL of acetone was added, and the mixture was stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 60 °C for 8 h to obtain 0.055 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with... Figure 1-2 Consistent.
[0178] Example 22 Preparation of crystal form A
[0179] 0.1 g of compound I was mixed with 0.5 mL of DMF and stirred at 40 °C until dissolved. 6 mL of acetonitrile and 4 mL of water were added, and the mixture was stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 60 °C for 12 h to obtain 0.061 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with... Figure 1-2 Consistent.
[0180] Example 23 Preparation of crystal form A
[0181] 0.1 g of compound I was mixed with 1 mL of DMF and stirred at 20 °C until dissolved. 1 mL of ethanol and 1 mL of water were added, and the mixture was stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 60 °C for 20 h to obtain 0.063 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with... Figure 1-2 Consistent.
[0182] Example 24 Preparation of crystal form A
[0183] 0.1 g of compound I was mixed with 1 mL of DMAC and stirred at 25 °C until dissolved. 2 mL of ethanol and 5 mL of water were added, and the mixture was stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 60 °C for 8 h to obtain 0.065 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with… Figure 1-2 Consistent.
[0184] Example 25 Preparation of crystal form A
[0185] 0.1 g of compound I was mixed with 1 mL of DMAC and stirred at 50 °C until dissolved. 2 mL of methanol was added, and the mixture was stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 50 °C for 12 h to obtain 0.067 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with... Figure 1-2 Consistent.
[0186] Example 26 Preparation of Crystal Form A
[0187] 0.1 g of compound I was mixed with 0.6 mL of DMAC and stirred at 20 °C until dissolved. 3 mL of ethanol and 7 mL of water were added, and the mixture was stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 50 °C for 24 h to obtain 0.072 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with... Figure 1-2 Consistent.
[0188] Example 27 Preparation of Crystal Form A
[0189] 0.1 g of compound I was mixed with 3 mL of DMAC and stirred at 30 °C until dissolved. 10 mL of water was added, and the mixture was stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 50 °C for 12 h to obtain 0.062 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with... Figure 1-2 Consistent.
[0190] Example 28 Preparation of crystal form A
[0191] 0.1 g of compound I was mixed with 5 mL of n-butanol to obtain a suspension, which was stirred at 40 °C for one day. The solid was separated, and the filter cake was vacuum dried at 60 °C for 24 h to obtain 0.071 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern were respectively compared with those of the compound I. Figure 1-2 Consistent.
[0192] Example 29 Preparation of Crystal Form A
[0193] 0.1 g of compound I was mixed with 0.2 mL of n-butanol to obtain a suspension, which was stirred at 5 °C for seven days. The solid was separated, and the filter cake was dried under vacuum at 60 °C for 8 hours to obtain 0.055 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern were respectively compared with those of compound I. Figure 1-2 Consistent.
[0194] Example 30 Preparation of crystal form A
[0195] 0.1 g of compound I was mixed with 1 mL of n-butanol to obtain a suspension, which was stirred at 15 °C for three days. The solid was separated, and the filter cake was dried under vacuum at 40 °C for 12 h to obtain 0.058 g of solid, which was crystal form A. Its X-ray powder diffraction pattern and DSC pattern were respectively compared with those of compound I. Figure 1-2 Consistent.
[0196] Example 31 Preparation of crystal form B
[0197] 0.1 g of compound I was mixed with 4 mL of 2-butanone to obtain a suspension. The mixture was stirred at 25 °C for one day. The solid was separated, and the filter cake was vacuum dried at 60 °C for 12 h to obtain 0.070 g of solid, which was crystal form B. Its X-ray powder diffraction pattern and DSC pattern were compared with those of the compound I. Figure 3-4 Consistent.
[0198] Example 32 Preparation of crystal form B
[0199] 0.1 g of compound I was mixed with 5 mL of n-heptane to form a suspension, stirred at 5 °C for seven days, the solid was separated, and the filter cake was dried under vacuum at 50 °C for 24 h to obtain 0.067 g of solid, which was crystal form B. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with those of compound I. Figure 3-4 As shown.
[0200] Example 33 Preparation of crystal form B
[0201] 0.1 g of compound I was mixed with 3 mL of butyl acetate to obtain a suspension. The mixture was stirred at 50 °C for two days, and the solid was separated. The filter cake was dried under vacuum at 60 °C for 24 h to obtain 0.071 g of solid, which was crystal form B. Its X-ray powder diffraction pattern and DSC pattern were respectively compared with those of the compound I. Figure 3-4Consistent.
[0202] Example 34 Preparation of crystal form B
[0203] 0.1 g of compound I was mixed with 2 mL of 1,4-dioxane to obtain a suspension. The mixture was stirred at 30 °C for three days. The solid was separated, and the filter cake was dried under vacuum at 40 °C for 8 hours to obtain 0.066 g of solid, which was crystal form B. Its X-ray powder diffraction pattern and DSC pattern were compared with those of the compound I. Figure 3-4 Consistent.
[0204] Example 35 Preparation of crystal form B
[0205] 0.1 g of compound I was mixed with 1 mL of water to obtain a suspension, which was stirred at 20 °C for one day. The solid was separated, and the filter cake was dried under vacuum at 60 °C for 24 h to obtain 0.075 g of solid, which was crystal form B. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with those of compound I. Figure 3-4 Consistent.
[0206] Example 36 Preparation of crystal form B
[0207] 0.1 g of compound I was mixed with 5 mL of isobutyl acetate to obtain a suspension, which was stirred at 50 °C for five days. The solid was separated, and the filter cake was vacuum dried at 30 °C for 24 h to obtain 0.074 g of solid, which was crystal form B. Its X-ray powder diffraction pattern and DSC pattern were respectively compared with those of the compound I. Figure 3-4 Consistent.
[0208] Example 37 Preparation of crystal form B
[0209] 0.1 g of compound I was mixed with 0.2 mL of isopropyl acetate to obtain a suspension, which was stirred at 15 °C for one day. The solid was separated, and the filter cake was vacuum dried at 20 °C for 12 h to obtain 0.054 g of solid, which was crystal form B. Its X-ray powder diffraction pattern and DSC pattern were respectively compared with those of the compound I. Figure 3-4 Consistent.
[0210] Example 38 Preparation of crystal form B
[0211] 0.1 g of compound I was mixed with 0.5 mL of methyl isobutyl ketone to obtain a suspension, which was stirred at 10 °C for three days. The solid was separated, and the filter cake was dried under vacuum at 40 °C for 8 hours to obtain 0.055 g of solid, which was crystal form B. Its X-ray powder diffraction pattern and DSC pattern were respectively compared with those of the compound I. Figure 3-4 Consistent.
[0212] Example 39 Preparation of Crystal Form B
[0213] 0.1 g of compound I was mixed with 0.5 mL of methyl isobutyl ketone and 0.5 mL of 2-butanone to obtain a suspension. The mixture was stirred at 40 °C for two days. The solid was separated, and the filter cake was vacuum dried at 50 °C for 12 h to obtain 0.051 g of solid, which was crystal form B. Its X-ray powder diffraction pattern and DSC pattern were compared with those of the compound I. Figure 3-4 Consistent.
[0214] Example 40 Preparation of crystal form B
[0215] 0.1 g of compound I was mixed with 1 mL of butyl acetate and 1 mL of isopropyl acetate to obtain a suspension. The mixture was stirred at 50 °C for one day, and the solid was separated. The filter cake was vacuum dried at 60 °C for 8 hours to obtain 0.061 g of solid, which was crystal form B. Its X-ray powder diffraction pattern and DSC pattern were compared with those of the compound I. Figure 3-4 Consistent.
[0216] Example 41 Preparation of crystal form B
[0217] 0.1 g of compound I was mixed with 3 mL of dichloromethane and stirred at 20 °C until dissolved. 1 mL of isobutyl acetate and 5 mL of n-heptane were added, and the mixture was stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 60 °C for 24 h to obtain 0.057 g of solid, which was crystal form B. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with... Figure 3-4 Consistent.
[0218] Example 42 Preparation of crystal form B
[0219] 0.1 g of compound I was mixed with 1 mL of dichloromethane and stirred at 30 °C until dissolved. 1 mL of isobutyl acetate and 1 mL of n-heptane were added, and the mixture was stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 20 °C for 8 h to obtain 0.055 g of solid, which was crystal form B. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with... Figure 3-4 Consistent.
[0220] Example 43 Preparation of crystal form B
[0221] 0.1 g of compound I was mixed with 2 mL of dichloromethane and stirred at 25 °C until dissolved. 3 mL of isobutyl acetate and 7 mL of n-heptane were added, and the mixture was stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 40 °C for 12 h to obtain 0.065 g of solid, which was crystal form B. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with… Figure 3-4 Consistent.
[0222] Example 44 Preparation of Crystal Form C
[0223] 0.1 g of compound I was mixed with 0.5 mL of DMAC to obtain a suspension. This suspension was stirred at 50 °C for 24 h, and the solid was separated. The filter cake was vacuum dried at 50 °C for 24 h to obtain 0.044 g of solid, which was crystalline form C. Its X-ray powder diffraction pattern and DSC pattern were compared with those of [other compounds]. Figure 5-6 Consistent.
[0224] Example 45 Preparation of Crystal Form C
[0225] 0.1 g of compound I was mixed with 0.2 mL of DMAC to obtain a suspension. This suspension was stirred at 55 °C for 8 h, and the solid was separated. The filter cake was vacuum dried at 20 °C for 12 h to obtain 0.041 g of solid, which was crystalline form C. Its X-ray powder diffraction pattern and DSC pattern were compared with those of [other compounds]. Figure 5-6 Consistent.
[0226] Example 46 Preparation of Crystal Form C
[0227] 0.1 g of compound I was mixed with 0.3 mL of DMAC to obtain a suspension. This suspension was stirred at 60 °C for 12 h, and the solid was separated. The filter cake was dried under vacuum at 60 °C for 8 h to obtain 0.046 g of solid, which was crystalline form C. Its X-ray powder diffraction pattern and DSC pattern were compared with those of [other compounds]. Figure 5-6 Consistent.
[0228] Example 47 Preparation of Crystal Form C
[0229] 0.1 g of compound I was mixed with 0.4 mL of DMAC to obtain a suspension. This suspension was stirred at 70 °C for 24 h, and the solid was separated. The filter cake was dried under vacuum at 50 °C for 24 h to obtain 0.045 g of solid, which was crystalline form C. Its X-ray powder diffraction pattern and DSC pattern were compared with those of [other compounds]. Figure 5-6 Consistent.
[0230] Example 48 Preparation of Crystal Form C
[0231] 0.1 g of compound I was mixed with 1 mL of DMAC and stirred at 60 °C until dissolved. 3 mL of n-butanol was added, and the mixture was stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 60 °C for 8 h to obtain 0.064 g of solid, which was crystalline form C. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with... Figure 5-6 As shown.
[0232] Example 49 Preparation of Crystal Form C
[0233] 0.1 g of compound I was mixed with 0.6 mL of DMAC and stirred at 70 °C until dissolved. 1 mL of isobutyl acetate was added, and the mixture was stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 30 °C for 12 h to obtain 0.063 g of solid, which was crystal form C. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with... Figure 5-6Consistent.
[0234] Example 50 Preparation of Crystal Form C
[0235] 0.1 g of compound I was mixed with 3 mL of DMAC and stirred at 55 °C until dissolved. 5 mL of acetone was added, and the mixture was stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 20 °C for 24 h to obtain 0.058 g of solid, which was crystal form C. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with... Figure 5-6 Consistent.
[0236] Example 51 Preparation of crystal form D
[0237] 0.1 g of compound I was mixed with 3 mL of DMF and stirred at 50 °C until dissolved. 2 mL of methanol was added, and the mixture was cooled to 20 °C and stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 60 °C for 12 h to obtain 0.055 g of solid, which was crystal form D. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with… Figure 7-8 As shown.
[0238] Example 52 Preparation of crystal form D
[0239] 0.1 g of compound I was mixed with 2 mL of DMF and stirred at 60 °C until dissolved. 5 mL of methanol was added, and the mixture was cooled to 30 °C and stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 20 °C for 24 h to obtain 0.058 g of solid, which was crystal form D. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with… Figure 7-8 Consistent.
[0240] Example 53 Preparation of crystal form D
[0241] 0.1 g of compound I was mixed with 1 mL of DMF and stirred at 70 °C until dissolved. 3 mL of methanol was added, and the mixture was cooled to 25 °C and stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 40 °C for 8 h to obtain 0.061 g of solid, which was crystal form D. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with… Figure 7-8 Consistent.
[0242] Example 54 Preparation of crystal form E
[0243] 0.1 g of compound I was mixed with 1 mL of DMF and stirred at 20 °C until dissolved. The solution was then added back to 2 mL of ethanol and 5 mL of water, and stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 60 °C for 8 h to obtain 0.056 g of solid, which was crystal form E. Its X-ray powder diffraction pattern and DSC pattern were compared with those of [other compounds]. Figure 9-10 As shown.
[0244] Example 55 Preparation of crystal form E
[0245] 0.1 g of compound I was mixed with 1 mL of DMF and stirred at 22 °C until dissolved. The solution was then added back to 1 mL of acetone and 5 mL of water, and stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 50 °C for 12 h to obtain 0.053 g of solid, which was crystal form E. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with… Figure 9-10 Consistent.
[0246] Example 56 Preparation of crystal form E
[0247] 0.1 g of compound I was mixed with 1 mL of DMF and stirred at 30 °C until dissolved. The solution was then added back to 2 mL of acetonitrile and 7 mL of water, and stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 20 °C for 24 h to obtain 0.061 g of solid, which was crystal form E. Its X-ray powder diffraction pattern and DSC pattern were compared with those of [other compounds]. Figure 9-10 Consistent.
[0248] Example 57 Preparation of crystal form E
[0249] 0.1 g of compound I was mixed with 0.5 mL of DMF and stirred at 30 °C until dissolved. Then, 1 mL of acetone and 1 mL of water were added, and the mixture was stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 40 °C for 12 h to obtain 0.062 g of solid, which was crystal form E. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with... Figure 9-10 Consistent.
[0250] Example 58 Preparation of crystal form E
[0251] 0.1 g of compound I was mixed with 2 mL of DMF and stirred at 25 °C until dissolved. The solution was then added back to 3 mL of acetonitrile and 7 mL of water, and stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 60 °C for 24 h to obtain 0.063 g of solid, which was crystal form E. Its X-ray powder diffraction pattern and DSC pattern were compared with those of [other compounds]. Figure 9-10 Consistent.
[0252] Example 59 Preparation of crystal form E
[0253] 0.1 g of compound I was mixed with 3 mL of DMAC and stirred at 22 °C until dissolved. The solution was then added back to 2 mL of ethanol and 5 mL of water, and stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 60 °C for 10 h to obtain 0.063 g of solid, crystal form E. Its X-ray powder diffraction pattern and DSC pattern are respectively compared with... Figure 9-10 Consistent.
[0254] Example 60 Preparation of crystal form E
[0255] 0.1 g of compound I was mixed with 1 mL of DMAC and stirred at 25 °C until dissolved. The solution was then added back to 3 mL of n-propanol and 6 mL of water, and stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 45 °C for 12 h to obtain 0.065 g of solid, which was crystal form E. Its X-ray powder diffraction pattern and DSC pattern were compared with those of [other compounds]. Figure 9-10 Consistent.
[0256] Example 61 Preparation of crystal form E
[0257] 0.1 g of compound I was mixed with 0.6 mL of DMAC and stirred at 20 °C until dissolved. The solution was then added back to 3 mL of n-propanol and 7 mL of water, and stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 20 °C for 24 h to obtain 0.069 g of solid, which was crystal form E. Its X-ray powder diffraction pattern and DSC pattern were compared with those of [other compounds]. Figure 9-10 Consistent.
[0258] Example 62 Preparation of crystal form E
[0259] 0.1 g of compound I was mixed with 2 mL of DMAC and stirred at 30 °C until dissolved. The solution was then added back to 3 mL of n-propanol and 5 mL of water, and stirred to induce crystallization. The solid was separated, and the filter cake was dried under vacuum at 50 °C for 8 h to obtain 0.066 g of solid, which was crystal form E. Its X-ray powder diffraction pattern and DSC pattern were compared with those of [other compounds]. Figure 9-10 Consistent.
[0260] Preparation of the amorphous form of compound I
[0261] The amorphous form of the compound of formula I prepared according to Example 5 of WO2017198221A1.
[0262] Stability test
[0263] The amorphous form of compound I prepared in the preparation examples, crystal form A of compound I prepared in Example 1, crystal form B of compound I prepared in Example 32, crystal form C of compound I prepared in Example 48, crystal form D of compound I prepared in Example 51, and crystal form E of compound I prepared in Example 54 were placed in environments of 75% RH, 92.5% RH, 40℃, 60℃, and light irradiation for 10 days, respectively. The X-ray powder diffraction patterns and purity of each crystal form were measured. The specific results are shown in Table 6 below:
[0264] Table 6
[0265] Crystal form A Crystal form B Crystal form C Crystal form D Crystal form E amorphous 0 days 99.87 99.75 99.72 99.55 99.56 95.33 75% RH for 10 days 99.85 99.75 99.71 99.54 99.56 94.93 92.5% RH for 10 days 99.83 99.73 99.68 99.54 99.54 94.83 40℃ for 10 days 99.83 99.69 99.66 99.52 99.53 94.67 60℃ for 10 days 99.81 99.72 99.66 99.49 99.52 94.73 10 days of sunlight 99.87 99.73 99.70 99.53 99.55 94.97
[0266] As shown in Table 6, compared with amorphous crystals, crystal forms A, B, C, D, and E have better stability and higher purity.
[0267] Particle size experiment
[0268] The particle size of the amorphous form of compound I prepared in the preparation examples, the crystal form A of compound I prepared in Example 1, the crystal form B of compound I prepared in Example 32, the crystal form C of compound I prepared in Example 48, the crystal form D of compound I prepared in Example 51, and the crystal form E of compound I prepared in Example 54 were measured respectively. The specific results are shown in Table 7 below:
[0269] Table 7
[0270] amorphous Crystal form A Crystal form B Crystal form C Crystal form D Crystal form E D50 2.68μm 22.37μm 21.98μm 21.77μm 20.98μm 20.98μm D90 22.82μm 72.86μm 71.56μm 70.88μm 70.49μm 69.99μm
[0271] The above results show that the amorphous particle size is significantly smaller than that of crystal forms A, B, C, D and E (where D50 is 2.68 μm, not exceeding 13% of the crystal form D50 of the present invention; and D90 is 22.82 μm, not exceeding 33% of the crystal form D90 of the present invention).
[0272] Liquidity Experiment
[0273] The amorphous form of compound I prepared in the preparation examples, the crystal form A of compound I prepared in Example 1, the crystal form B of compound I prepared in Example 32, the crystal form C of compound I prepared in Example 48, the crystal form D of compound I prepared in Example 51, and the crystal form E of compound I prepared in Example 54 were measured, and their angles of repose were measured respectively. The specific results are shown in Table 8 below:
[0274] Table 8
[0275] amorphous Crystal form A Crystal form B Crystal form C Crystal form D Crystal form E 1 43.3° 33.4° 34.6° 34.2° 35.6° 35.5° 2 42.6° 31.8° 35.7° 35.4° 36.2° 36.1° 3 41.9° 33.7° 35.2° 33.9.° 35.1° 35.9°
[0276] The above results indicate that the angle of repose of the amorphous form is significantly larger than that of crystal forms A, B, C, D, and E, suggesting that crystal forms A, B, C, D, and E are significantly superior to the amorphous form in terms of fluidity.
[0277] Hygroscopicity test
[0278] The amorphous form of compound I prepared in the preparation examples, the crystalline form A of compound I prepared in Example 1, the crystalline form B of compound I prepared in Example 32, the crystalline form C of compound I prepared in Example 48, the crystalline form D of compound I prepared in Example 51, and the crystalline form E of compound I prepared in Example 54 were placed in an environment of 75% RH and 25°C for 24 hours, their weights were measured, and their hygroscopicity was calculated. The specific results are shown in Table 9 below:
[0279] Table 9
[0280] amorphous Crystal form A Crystal form B Crystal form C Crystal form D Crystal form E hygroscopic 0.52% 0.10% 0.12% 0.15% 0.16% 0.20%
[0281] The above results indicate that the hygroscopicity of the amorphous form is significantly greater than that of crystal forms A, B, C, D, and E, suggesting that crystal forms A, B, C, D, and E are significantly superior to the amorphous form in terms of hygroscopicity.
[0282] Those skilled in the art will understand that the numerical values or numerical endpoints involved in the technical solutions of this invention are not limited to the numbers themselves, but include those permissible error ranges that are widely accepted in the art, such as experimental errors, measurement errors, statistical errors, and random errors, etc., and these error ranges are all included within the scope of this invention.
[0283] Those skilled in the art will recognize that many modifications and variations can be made to the invention without departing from its spirit and scope. The specific embodiments described herein are provided by way of example only and are not intended to limit the scope in any way. The true scope and spirit of the invention are shown in the appended claims, and the description and embodiments are merely exemplary.
Claims
1. A crystal form A of a compound of formula I, Formula I Its features are, Using Cu-Kα radiation, its X-ray powder diffraction pattern, expressed in degrees as 2θ, has characteristic peaks at 7.3±0.2°, 8.4±0.2°, 9.7±0.2°, 12.4±0.2°, 16.7±0.2°, and 19.5±0.2°.
2. The crystal form A according to claim 1, characterized in that, Using Cu-Kα radiation, the X-ray powder diffraction patterns, expressed in degrees as 2θ, are obtained at 5.3±0.2°, 7.3±0.2°, 8.4±0.2°, 9.7±0.2°, 12.0±0.2°, 12.4±0.2°, 15.1±0.2°, 15.4±0.2°, 16.3±0.2°, 16.7±0.2°, 17.1±0.2°, 17.9±0.2°, 18.9±0.2°, 19.5±0.2°, 21.1±0.2°, and 21.7±0.2°. Characteristic peaks are observed at 22.7±0.2°, 23.1±0.2°, 23.5±0.2°, 24.8±0.2°, 25.4±0.2°, 25.8±0.2°, 26.3±0.2°, 27.1±0.2°, 27.7±0.2°, 28.2±0.2°, 28.6±0.2°, 29.0±0.2°, 30.9±0.2°, 31.5±0.2°, 32.7±0.2°, 34.1±0.2°, 35.9±0.2°, and 38.1±0.2°.
3. Crystal form A according to claim 1 or 2, characterized in that, Its X-ray powder diffraction pattern is basically as shown in Figure 1.
4. A method for preparing crystal form A as described in any one of claims 1-3, characterized in that, The method is selected from any of the following methods: Method (1): Mix the compound of formula I with an organic solvent to obtain a suspension. Stir the suspension at 5-50℃ for 1-7 days, separate the solid, and vacuum dry at 20-60℃ for 8-24 hours to obtain crystal form A. The organic solvent is selected from one or more of C1-C3 alcohols, methyl acetate, ethyl acetate, acetone, and acetonitrile. The weight-to-volume ratio of the compound of formula I to the organic solvent in method (1) is 1:2 to 1:50 (g / mL). Method (2): Mix the compound of formula I with DMSO or dichloromethane, stir at 20-50℃ until dissolved, add a poor solvent, stir to crystallize, separate the solid, and vacuum dry at 20-60℃ for 8-24h to obtain crystal form A. The poor solvent is selected from one or more of C1-C4 alcohols, methyl acetate, ethyl acetate, butyl acetate, isopropyl acetate, acetone, acetonitrile, water, and alkanes. The weight-to-volume ratio of the compound of formula I described in method (2) to DMSO or dichloromethane is 1:10-1:40 (g / mL). Method (3): Mix the compound of formula I with DMF, stir at 20-50℃ until dissolved, add a poor solvent, stir to crystallize, separate the solid, and vacuum dry at 20-60℃ for 8-24h to obtain crystal form A; The weight-to-volume ratio of the compound of formula I to DMF in method (3) is 1:5-1:20 (g / mL). Method (4): Mix the compound of formula I with DMAC, stir at 20-50℃ until dissolved, add a poor solvent, stir to crystallize, separate the solid, and vacuum dry at 20-60℃ for 8-24h to obtain crystal form A. The weight-volume ratio of the compound of formula I to DMAC is 1:6-1:30 (g / mL). Method (5): Mix the compound of formula I with n-butanol to obtain a suspension. Stir the suspension at 5-40℃ for 1-7 days to obtain a crystal slurry. Separate the solid and vacuum dry at 20-60℃ for 8-24 hours to obtain crystal form A. The weight-to-volume ratio of the compound of formula I described in method (5) to n-butanol is 1:2-1:50 (g / mL).
5. The method for crystal form A as described in claim 4, characterized in that, The C1-C3 alcohols mentioned in method (1) are selected from methanol, ethanol, n-propanol or isopropanol.
6. The method for crystal form A as described in claim 4, characterized in that, The C1-C4 alcohols mentioned in method (2) are selected from methanol, ethanol or isopropanol, and the alkanes are selected from n-heptane, n-hexane or cyclohexane.
7. The method for crystal form A as described in claim 4, characterized in that, The weight-to-volume ratio of the compound of formula I described in method (2) to the unsuitable solvent is 1:20-1:130 (g / mL).
8. The method for crystal form A as described in claim 4, characterized in that, The undesirable solvents described in method (3) are selected from one or more of C2-C4 alcohols, isopropyl acetate, acetone, acetonitrile, and water.
9. The method for crystal form A as described in claim 4, characterized in that, The C2-C4 alcohols mentioned in method (3) are selected from ethanol or isopropanol.
10. The method for crystal form A as described in claim 4, characterized in that, The weight-to-volume ratio of the compound of formula I to the unsuitable solvent in method (3) is 1:20-1:100 (g / mL).
11. The method for crystal form A as described in claim 4, characterized in that, The undesirable solvents described in method (4) are selected from one or more of C1-C4 alcohols and water.
12. The method for crystal form A as described in claim 4, characterized in that, The C1-C4 alcohols mentioned in method (4) are selected from methanol, ethanol or isopropanol.
13. The method for crystal form A as described in claim 4, characterized in that, The weight-to-volume ratio of the compound of formula I described in method (4) to the unsuitable solvent is 1:20-1:100 (g / mL).
14. A crystal form B of a compound of formula I, Formula I Its features are, Using Cu-Kα radiation, its X-ray powder diffraction pattern, expressed in degrees as 2θ, has characteristic peaks at 7.9±0.2°, 9.4±0.2°, 10.1±0.2°, 11.9±0.2°, 14.4±0.2°, 16.1±0.2°, and 19.0±0.2°.
15. Crystal form B according to claim 14, characterized in that, Using Cu-Kα radiation, the X-ray powder diffraction patterns, expressed in degrees as 2θ, are obtained at 7.9±0.2°, 9.4±0.2°, 10.1±0.2°, 11.9±0.2°, 12.5±0.2°, 12.8±0.2°, 13.5±0.2°, 14.4±0.2°, 14.8±0.2°, 15.2±0.2°, 16.1±0.2°, 16.9±0.2°, 18.4±0.2°, 19.0±0.2°, and 19.3±0.2°. Characteristic peaks are observed at 19.7±0.2°, 20.3±0.2°, 20.7±0.2°, 21.4±0.2°, 21.7±0.2°, 22.4±0.2°, 23.3±0.2°, 24.0±0.2°, 24.5±0.2°, 25.0±0.2°, 25.4±0.2°, 25.9±0.2°, 26.4±0.2°, 27.6±0.2°, 28.5±0.2°, 31.2±0.2°, and 33.2±0.2°.
16. Crystal form B according to claim 14 or 15, characterized in that, Its X-ray powder diffraction pattern is basically as shown in Figure 3.
17. A method for preparing crystal form B as described in any one of claims 14-16, characterized in that, The method is selected from any of the following methods: Method (1): Mix the compound of formula I with dichloromethane, stir at 20-30℃ until dissolved, add a poor solvent, stir to crystallize, separate the solid, and vacuum dry at 20-60℃ for 8-24h to obtain crystal form B. The poor solvent is a mixture of isobutyl acetate and n-heptane. The weight-to-volume ratio of the compound of formula I described in method (1) to dichloromethane is 1:10-1:30 (g / mL). Method (2): Mix the compound of formula I with a solvent to obtain a suspension. Stir the suspension at 5-50℃ for 1-7 days, separate the solid, and vacuum dry at 20-60℃ for 8-24 hours to obtain crystal form B. The solvent is selected from one or more of 2-butanone, methyl isobutyl ketone, 1,4-dioxane, butyl acetate, isopropyl acetate, isobutyl acetate, n-heptane, n-hexane, cyclohexane, and water. The weight-to-volume ratio of the compound of formula I to the solvent in method (2) is 1:2-1:50 (g / mL).
18. A method for crystal form B as described in claim 17, characterized in that, The weight-to-volume ratio of the compound of formula I in method (1) to the unsuitable solvent is 1:20-1:100 (g / mL).
19. A crystal form C of a compound of formula I, Formula I Its features are, Using Cu-Kα radiation, its X-ray powder diffraction pattern, expressed in degrees as 2θ, shows characteristic peaks at 7.3±0.2°, 12.4±0.2°, 12.8±0.2°, 14.8±0.2°, 18.4±0.2°, 19.5±0.2°, and 23.0±0.2°.
20. The crystal form C according to claim 19, characterized in that, Using Cu-Kα radiation, the X-ray powder diffraction patterns, expressed in degrees as 2θ, are obtained at 3.6±0.2°, 7.3±0.2°, 10.6±0.2°, 11.0±0.2°, 11.3±0.2°, 11.8±0.2°, 12.4±0.2°, 12.8±0.2°, 13.6±0.2°, 14.3±0.2°, 14.8±0.2°, 16.8±0.2°, 17.7±0.2°, 18.0±0.2°, and 18.4±0.2°. Characteristic peaks are observed at °, 19.5±0.2°, 20.3±0.2°, 20.8±0.2°, 21.4±0.2°, 22.0±0.2°, 23.0±0.2°, 23.3±0.2°, 23.9±0.2°, 24.3±0.2°, 24.7±0.2°, 26.0±0.2°, 26.9±0.2°, 27.5±0.2°, 28.2±0.2°, 29.0±0.2°, 30.0±0.2°, and 31.4±0.2°.
21. The crystal form C according to claim 19 or 20, characterized in that, Its X-ray powder diffraction pattern is basically as shown in Figure 5.
22. A method for preparing crystal form C as described in any one of claims 19-21, characterized in that, The method is selected from any of the following methods: Method (1): Mix the compound of formula I with DMAC to obtain a suspension. Stir the suspension at 50-70℃ for 8-24h, separate the solid, and dry it under vacuum at 20-60℃ for 8-24h to obtain crystal form C. The weight-volume ratio of the compound of formula I to DMAC is 1:2-1:5 (g / mL). Method (2): Mix the compound of formula I with DMAC, stir at 55-70℃ until dissolved, add a poor solvent, stir to crystallize, separate the solid, and vacuum dry at 20-60℃ for 8-24h to obtain crystal form C. The weight-volume ratio of the compound of formula I to DMAC is 1:6-1:30 (g / mL).
23. A method for crystal form C as described in claim 22, characterized in that, The undesirable solvents mentioned in method (2) are selected from n-propanol, isopropanol, n-butanol, C3-C6 esters or acetone.
24. A method for crystal form C as described in claim 17, characterized in that, The C3-C6 esters described in method (2) are selected from methyl acetate, ethyl acetate, isopropyl acetate or isobutyl acetate.
25. A method for crystal form C as described in claim 17, characterized in that, The weight-to-volume ratio of the compound of formula I to the unsuitable solvent in method (2) is 1:10-1:50 (g / mL).
26. A crystal form D of a compound of formula I, Formula I Its features are, Using Cu-Kα radiation, its X-ray powder diffraction pattern, expressed in degrees as 2θ, has characteristic peaks at 3.5±0.2°, 7.0±0.2°, 13.4±0.2°, 15.7±0.2°, 16.6±0.2°, and 20.6±0.2°.
27. The crystal form D according to claim 26, characterized in that, Using Cu-Kα radiation, the X-ray powder diffraction patterns, expressed in degrees as 2θ, are obtained at 3.5±0.2°, 7.0±0.2°, 10.5±0.2°, 11.0±0.2°, 11.5±0.2°, 12.0±0.2°, 12.4±0.2°, 13.4±0.2°, 14.0±0.2°, 14.4±0.2°, 15.7±0.2°, 16.6±0.2°, 17.7±0.2°, 18.3±0.2°, and 18.6±0.2°. Characteristic peaks are observed at 20.1±0.2°, 20.6±0.2°, 21.2±0.2°, 21.7±0.2°, 22.1±0.2°, 22.4±0.2°, 23.3±0.2°, 24.3±0.2°, 24.9±0.2°, 25.9±0.2°, 27.0±0.2°, 27.3±0.2°, 28.4±0.2°, 29.0±0.2°, 29.3±0.2°, 30.1±0.2°, and 31.7±0.2°.
28. The crystal form D according to claim 26 or 27, characterized in that, Its X-ray powder diffraction pattern is basically as shown in Figure 7.
29. A method for preparing crystal form D as described in any one of claims 26-28, characterized in that, The method includes: The compound of formula I was mixed with DMF and stirred at 50-70℃ until dissolved. Methanol was added, and the mixture was cooled to 20-30℃ and stirred to crystallize. The solid was separated and dried under vacuum at 20-60℃ for 8-24 hours to obtain crystal form D. The weight-to-volume ratio of the compound of Formula I to DMF is 1:10 to 1:30 (g / mL).
30. A method for crystal form D as described in claim 29, characterized in that, The weight-to-volume ratio of the compound of Formula I to methanol is 1:20-1:50 (g / mL).
31. A crystal form E of a compound of formula I, Formula I Its features are, Using Cu-Kα radiation, its X-ray powder diffraction pattern, expressed in degrees as 2θ, shows characteristic peaks at 3.5±0.2°, 7.0±0.2°, 13.5±0.2°, 15.2±0.2°, 16.3±0.2°, 17.5±0.2°, and 28.7±0.2°.
32. The crystal form E according to claim 31, characterized in that, Using Cu-Kα radiation, the X-ray powder diffraction patterns, expressed in degrees as 2θ, are obtained at 3.5±0.2°, 7.0±0.2°, 10.5±0.2°, 11.0±0.2°, 11.6±0.2°, 11.9±0.2°, 12.4±0.2°, 13.5±0.2°, 13.7±0.2°, 14.4±0.2°, 15.2±0.2°, 16.3±0.2°, 16.9±0.2°, 17.5±0.2°, 18.2±0.2°, and 18.8±0.2°. Characteristic peaks are observed at °, 19.6±0.2°, 20.2±0.2°, 20.8±0.2°, 21.3±0.2°, 21.8±0.2°, 22.1±0.2°, 22.8±0.2°, 23.2±0.2°, 23.6±0.2°, 25.0±0.2°, 25.4±0.2°, 26.5±0.2°, 27.3±0.2°, 27.7±0.2°, 28.7±0.2°, 29.3±0.2°, 30.2±0.2°, and 31.3±0.2°.
33. The crystal form E according to claim 17 or 18, characterized in that, Its X-ray powder diffraction pattern is basically as shown in Figure 9.
34. A method for preparing crystal form E as described in any one of claims 31-33, characterized in that, The method is selected from any of the following methods: Method (1): Mix the compound of formula I with DMF, stir at 20-30℃ until dissolved, then add back to a poor solvent, stir to crystallize, separate the solid, and vacuum dry at 20-60℃ for 8-24h to obtain crystal form E; The weight-to-volume ratio of the compound of formula I to DMF in method (1) is 1:5-1:20 (g / mL). Method (2): Mix the compound of formula I with DMAC, stir and dissolve at 20-30℃, then add back to a poor solvent, stir to crystallize, separate the solid, and vacuum dry at 20-60℃ for 8-24h to obtain crystal form E. The weight-volume ratio of the compound of formula I to DMAC is 1:6-1:30 (g / mL).
35. A method for crystal form E as described in claim 34, characterized in that, The unsuitable solvents mentioned in method (1) are selected from a mixture of ethanol, acetone, acetonitrile and water.
36. A method for crystal form E as described in claim 34, characterized in that, The weight-to-volume ratio of the compound of formula I in method (1) to the unsuitable solvent is 1:20-1:100 (g / mL).
37. A method for crystal form E as described in claim 34, characterized in that, The undesirable solvent mentioned in method (2) is selected from a mixture of ethanol, n-propanol and water.
38. A method for crystal form E as described in claim 34, characterized in that, The weight-to-volume ratio of the compound of formula I described in method (2) to the unsuitable solvent is 1:70-1:100 (g / mL).
39. A pharmaceutical composition comprising a therapeutically effective amount of crystal form A according to any one of claims 1-3, crystal form B according to any one of claims 14-16, crystal form C according to any one of claims 19-21, crystal form D according to any one of claims 26-28, and crystal form E according to any one of claims 31-33.
40. Use of crystal form A according to any one of claims 1-3, crystal form B according to any one of claims 14-16, crystal form C according to any one of claims 19-21, crystal form D according to any one of claims 26-28, crystal form E according to any one of claims 31-33, or the pharmaceutical composition according to claim 39 in the preparation of a medicament for treating a disease of cancer, wherein said disease is non-small cell lung cancer, gastric cancer, multiple myeloma, liver cancer, or cholangiocarcinoma.
41. Use of crystal form A according to any one of claims 1-3, crystal form B according to any one of claims 14-16, crystal form C according to any one of claims 19-21, crystal form D according to any one of claims 26-28, crystal form E according to any one of claims 31-33, or the pharmaceutical composition according to claim 39 in the preparation of a medicament for treating cancer, wherein said disease is liver cancer and bile duct cancer.
Citation Information
Patent Citations
Pyrimidine FGFR4 inhibitors
WO2015057938A1
FGFR4 inhibitors
WO2015057963A1
Ring-fused bicyclic pyridyl derivatives as FGFR4 inhibitors
WO2015059668A1
FGFR4 inhibitor and application thereof
CN109422760A
Pyrimidine derivative, method for preparing same and use thereof in medicine
WO2017198221A1